Jaminan Sosial Bagi Tenaga Kerja Indonesia (Mencari Pelajaran Dari Implementasi Kebijakan di Berbagai Negara) - Anita Kristina (MediaTrend, 2018)
The purpose of this study is to review the social security policy for Indonesian workers and various implementations of social protection policies in some countries. Qualitative descriptive approach as the appropriate method, because this review is used to look at the social security policy of migrant workers as a whole. This review does not focus on specific steps, but describes the foundations and orientations of policies promoted by some countries, particularly in providing protection for migrant workers. Findings on the results of this review show that implementation of social security policies for labor migrants require change as a policy evaluation context. This is as a new hope for the design of protection received by migrant workers based on implementation reviews from various countries.